Effect and fate study with blue mussels and microplastic in a laboratory experiment: fate experiment - Aurelia Laubscher; Thea Hamm; Mark Lenz (PANGAEA, 2021)
Adult blue mussels (Mytilus spp.) were exposed to microplastic particles in a controlled laboratory experiment. The fate of PS beads within the experimental set up was assessed in four compartments (exposure water, depuration water, feces, softbody) after 2 hours of exposure, 24 hours and 48 hours of depuration in filtered sea water. Additionally, the loss of microplastic as the difference of the sum of all recovered PS beads and the measured concentration at the start of the experiment was determined to obtain a complete mass balance. The total number of PS beads and the number of PS beads per unit as well as the percentage recovery is given.
In: Laubscher, A et al. (2021): Effect and fate study with blue mussels and microplastic in a laboratory experiment [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.937475